Smart Dental Card Game Model as An Effort to Improve Behavior of Health Care For Elementary School Students - lely Surya Ningsih; Bedjo Santoso; Tri Wiyatini; Diyah Fatmasari; Waljuni A Rahman (International Journal of Nursing and Health Services (IJNHS), 2020)
Correct teeth brushing behavior in elementary school children in Indonesia is 2.8%, and in Central Java, 1.7%. The influencing factor is the lack of information sources, so it is essential to carry out dental and oral health education, "Smart dental card game model" provides learning to children through game methods so that the learning process is more exciting and enjoyable. To produce a gamification-based dental and oral health education model called "Smart dental card game model" to increase dental health maintenance knowledge and decrease the debris index score in elementary school children. Research and development (R&D) and model trials using quasi-experiment pre-test and post-test with control sample design groups were divided into two groups, 28 intervention group students and 28 control group students. The dependent variable is the knowledge and debris index of elementary school students; the independent variable is the Smart dental card game model. The sample size was calculated by using the slovin formula. Data were tested using the interclass correlation coefficient test, Anova, Wilcoxon, Mann Whitney. The smart dental card game was appropriate as a guideline in the learning process to increase elementary school students' knowledge of 2,304 ± 9.07 and reduce the debris index of 0.419 ± 0.68 compared to the control group flipchart media and dental phantom. Smart dental card game is useful to increase dental health maintenance knowledge of elementary school students